Application of hyperspectral remote sensing in mineral identification and mapping - Zhang Ting-ting; Liu Fei (2012 2nd International Conference on Computer Science and Network Technology, 2012)
Hyperspectral remote sensing technology can identify mineral finely compared with traditional remote sensing techniques since many tens of bands are recorded in hyperspectral images and made it possible to construct a complete reflectance spectrum of every pixel in the scene. Geological remote sensing, as a kind of foundation work in geological survey, plays an important role in mineral prospection and exploration. This paper takes porphyry copper deposit as a typical example to explain the basic principles of hyperspectral remote sensing in deposit exploration. Different minerals, especially the altered minerals in certain ore deposit have diagnostic spectral features in remote sensing images, by which the regularity of ore formation can be deduced.